2019
DOI: 10.7150/jca.33486
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in miRNA genes play roles in the initiation and development of cervical cancer

Abstract: MicroRNA deregulation is crucial for cancer development. Studies showed that polymorphisms in miRNA genes could affect miRNA expression, which might be associated with cancer development. In the current study, we investigated the association of seven single nucleotide polymorphisms (SNPs) in seven miRNA genes with the initiation and development of cervical cancer in a Chinese Han population. The SNPs of 358 cervical intraepithelial neoplasia (CIN) patients, 547 cervical cancer patients and 567 healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 61 publications
0
22
0
Order By: Relevance
“…The restoration of miR-218 significantly inhibited the proliferation, migration, and invasion of cancer cells [37]. Laminin-5 β3 (LAMB3) has been verified as a transcriptional target of miR-218 [38], and the expression of LAMB3 is increased in the presence of the HPV-16 E6 oncoprotein, and this effect is mediated by miR-218 [19]. The miR-196a2 is located on the human chromosome 12q13.13.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The restoration of miR-218 significantly inhibited the proliferation, migration, and invasion of cancer cells [37]. Laminin-5 β3 (LAMB3) has been verified as a transcriptional target of miR-218 [38], and the expression of LAMB3 is increased in the presence of the HPV-16 E6 oncoprotein, and this effect is mediated by miR-218 [19]. The miR-196a2 is located on the human chromosome 12q13.13.…”
Section: Discussionmentioning
confidence: 99%
“…After reading the titles and the abstracts, 235 articles were excluded, of which 61 were duplicate ones, 149 had no relation to this topic, 22 were reviews or metaanalyses, and 3 were conference abstracts. Finally, 12 eligible case-control studies were included in our meta-analysis (Table 1) [10][11][12][13][14][15][16][17][18][19][20][21].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al . reported that rs4636297 in miR-126, which was located 12 bp downstream of the pre-miR-126 sequence, was associated with CIN and cervical cancer in a Chinese Han population 66 . The results of the study by Yan et al .…”
Section: The Roles Of Mirnas and Their Snps In Cervical Cancermentioning
confidence: 98%
“…The results of the study by Yan et al . indicated that the T allele confers a higher risk of developing CIN and cervical cancer 66 . The association of the SNP rs4636297 with cervical cancer may be because the SNP is related to Drosha's recognition and cleavage of pri-miRNA 34 .…”
Section: The Roles Of Mirnas and Their Snps In Cervical Cancermentioning
confidence: 99%